Development of a Menu of Mangroves to Increase Knowledge of the Mangrove Ecotourism Group (Pokdarwis) Sekotong West Lombok - Al-Idrus, Agil; Bayani, Faizul; Ferniawan, Ferniawan; Swati, Ni Nengah Sri; Rahmawati, Sri; Liswijaya, Liswijaya; Wardani, Intan Kusuma (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Mangrove ecotourism in Sekotong, Lombok Barat, holds immense potential for education and local economic development. However, there are still limitations in effectively communicating mangrove education information to tourists and local communities. This study aims to determine the role of